Contributions To Evaluate Design Investment In Portuguese Orange From Silves - Pias, Filipa (Journal of Tourism, Sustainability and Well-being, 2016)
Food reminds us every day that we are a part of nature and with our daily choices it is we who preserve or not biodiversity and species. It is we who promote or not the production of more health and fresh food. In an increasingly informed society about the benefits of having a balanced diet, meals started to be seen as tasting flavours and aromas, a moment of well-being, where the origin, production and method of preparation of agricultural products play a leading role. Because the market has changed, it is no longer anonymous it became personalized and essentially motivated by what you can enjoy, which implies a willingness to participate and build its own experience. In general, the companies believe that design collaboration is an advantage but if they do not have means of measuring design’s cost/benefit, it will not be easy to understand design as an investment that brings value to business. The purpose of this research is to draw the attention for the importance of design management, by evaluating the return of design’s investment in the Portuguese agro-food industry and by developing a model that allows them to assess the return on investment in design.